The great fire [videorecording (DVD)] - Buchan, Andrew, 1979-; Huston, Jack, 1982-; Leslie, Rose, 1987- (PBS Distribution, 2015)
The Great Fire of London raged for four days in 1666, making over 70,000 of the city's 80,000 inhabitants homeless. From King Charles II and Samuel Pepys to Thomas Farriner, the King's baker, in whose premises the fire began, witness the chaos of a city imploding, and the fear and rumors of treachery that took hold.